In vitro Bioaccessibility and Intestinal Absorption of Selected Bioactive Compounds in Terminalia ferdinandiana - Akter, Saleha; Addepalli, Rama; Netzel, Michael; Tinggi, Ujang; Fletcher, Mary; Sultanbawa, Yasmina; Osborne, Simone (Frontiers in Nutrition, 2022)
Terminalia ferdinandiana (or Kakadu plum), a native Australian fruit with potential health benefits, contains bioactive compounds such as ellagic acid (EA), ascorbic acid (AA) and calcium, and antinutrients such as oxalic acid (OA). However, few is known about the biological fate of these compounds following ingestion; therefore, the aim of this study was to evaluate in vitro bioaccessibility and intestinal absorption of T. ferdinandiana compounds using the INFOGEST static digestion model and Caco-2-HT29-MTX-E12 intestinal absorption model. No significant changes (p > 0.05) were observed in total AA content throughout in vitro digestion, whereas bioaccessibility of EA, OA, and calcium increased significantly from 33, 72, and 67% in the gastric phase to 48, 98, and 90% in the intestinal phase, respectively. The intestinal absorption study revealed variable rates of movement across the cell barrier. Findings reveal novel and important insights for the prediction of in vivo bioavailability of selected T. ferdinandiana compounds.